2011
DOI: 10.1002/ca.21100
|View full text |Cite
|
Sign up to set email alerts
|

Sigmoid colon morphology in the population groups of Durban, South Africa, with special reference to sigmoid volvulus

Abstract: Sigmoid volvulus demonstrates geographical, racial, and gender variation. This autopsy study was undertaken to establish morphological differences of the sigmoid colon and its mesocolon in which the length and other characteristics were assessed. A total of 590 cadavers were examined (403 African, 91 Indian, and 96 White). Length and height of the sigmoid colon and mesocolon were significantly longer in Africans, and mesocolon root was significantly narrower in Africans. Mesocolic ratio for Africans, Indians, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
37
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 22 publications
4
37
3
Order By: Relevance
“…In a radiological study done among the Calabar community in Nigeria, Bassey suggested that chronic use of enema along with the instrumentations used to deliver the concoction results in the lengthening of loop [10]. This could be responsible for a similar finding by Madiba et al, [5] belonging to the same continent.…”
Section: Comparison Of Length Of Sigmoid Colonmentioning
confidence: 85%
See 3 more Smart Citations
“…In a radiological study done among the Calabar community in Nigeria, Bassey suggested that chronic use of enema along with the instrumentations used to deliver the concoction results in the lengthening of loop [10]. This could be responsible for a similar finding by Madiba et al, [5] belonging to the same continent.…”
Section: Comparison Of Length Of Sigmoid Colonmentioning
confidence: 85%
“…Haffajee [5]. The classical type of sigmoid colon was the one that lies close to the pelvic brim with the normal anatomical textbook description.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This report matches with the long-narrow type description of Madiba and Haffajee. [9] Madiba and Haffajee also classified the sigmoid colon in reference to the pelvic brim as pelvic and suprapelvic positions; [9] our case falls in to the category of suprapelvic type. Nayak et al [2] reported a case of sigmoid colon where it occupied the median position in the lesser pelvis, completely filling the rectovesical pouch and covering the superior aspect of the urinary bladder.…”
Section: Discussionmentioning
confidence: 60%